Cultural-Historical Psychology (L.S.Vygotsky, A.R.Luria, A.N. Leontiev) Based on the Activity Approach of V.V.Davydov in the Program of V.V. Rubtsov's Development of Socio-Genetic Psychology - Gromyko, Y.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2025)
The article presents a review analysis of V.V.Rubtsov's monograph Socio-Genetic Psychology of Educational Interactions. Selected Articles, Speeches, Projects. The author examines the most important results of the implementation of the research program of V.V.Rubtsov's socio-genetic psychology. The author believes that V.V. Rubtsov's fundamental research has confirmed the innovative and revolutionary nature of developmental education proposed by V.V. Davydov and D.B. Elkonin. Also, these studies helped Rubtsov to put forward several important ideas for modern educational policy. These include the development of the Russian School of the Future concept (together with Y.V. Gromyko, V.A. Guruzhapov, and A.A. Margolis), social policy for better childhood conditions, the development of inclusive education for children with special needs, the education for future research psychologists, and the introduction of digital technologies in education. By investigating various forms of learning interaction in the system of developmental education, V.V. Rubtsov clarified and concretized the basic principles of cultural-historical psychology, as well as highlighted the most important problems that require further solution. В статье излагается обзорный анализ монографии В.В. Рубцова «Социально-генетическая психология учебных взаимодействий (избранные статьи, выступления, проекты)». Автор рассматривает важнейшие результаты реализации исследовательской программы социально-генетической психологии В.В. Рубцова. С точки зрения автора статьи, результаты фундаментальных исследований В.В. Рубцова позволили ему обосновать и доказать опережающе-революционный характер практики развивающего образования В.В. Давыдова-Д.Б. Эльконина, а также выдвинуть ряд важнейших положений в области современной образовательной политики, касающихся проблем разработки проекта Российской школы будущего (совместно с Ю.В. Громыко, В.А. Гуружаповым, А.А. Марголисом), социальной политики в интересах детей для обеспечения благополучного детства, инклюзивного образования детей с особыми нуждами, фундаментальной подготовки психологов-исследователей, цифровизации образования. В результате реализованной В.В. Рубцовым фундаментальной программы исследований различных форм учебных взаимодействий в практиках развивающего образования В.В. Давыдова, как считает автор статьи, были уточнены и конкретизированны основные положения культурно-исторической психологии, а также сформулированы важнейшие проблемы ее развития.